Examining the immunoepigenetic-gut microbiome axis in the context of self-esteem among Native Hawaiians and other Pacific Islanders - Becerra, Celyna Y.; Wells, Riley K.; Kunihiro, Braden P.; Lee, Rosa H.; Umeda, Lesley; Allan, Nina P.; Rubas, Noelle C.; McCracken, Trevor A.; Nunokawa, Chandler K. L.; Lee, Ming-Hao; Pidlaoan, Felix Gerard S.; Phankitnirondorn, Krit; et al. (Frontiers in Genetics, 2023)
Native Hawaiians and other Pacific Islanders (NHPIs) experience disparities in mental health, as they have a higher prevalence of having depressed moods, suicidal thoughts and attempts, and illicit drug usage compared to Non-Hispanic White People. While existing literature describes social determinants of mental health in this population, little is known about the biological mechanisms underlying the disproportionately higher rates of low self-esteem (LSE) related to depression among NHPIs. Herein, we investigated the immunoepigenetic-gut microbiome axis in a cohort enriched with NHPI participants who provided biospecimens and completed a questionnaire containing the Rosenberg self-esteem scale (SE score) in our community-based study. We observed that compared to individuals with normal self-esteem (NSE), those with LSE exhibited significantly higher plasma concentrations (pg/ml) of proinflammatory chemokine IL-8 (P=0.051) and cytokine TNF-ɑ (P=0.011). Using 16s-based sequencing, we identified associations of specific gut bacteria whose relative abundance significantly varied between the SE groups and correlated with SE score. Microbial diversity measured by Chao-1, Shannon, and Simpson indices did not exhibit any differences between the SE groups at the family, genus, and species levels. Interestingly, from monocytes enriched from blood samples of each participant, we analyzed DNA methylation using Infinium MethylationEPIC BeadChip (Illumina) and identified 104 CpGs that were differentially methylated between normal and low self-esteem groups and were preferentially involved in biological processes related to metabolism based on Gene Ontology analysis. Altogether, these data reveal novel differences in the immunoepigenetic-gut microbiome axis that relates to self-esteem among NHPIs and implicates this axis in the pathology of mental health conditions including depression, warranting further investigation.